The Islamic worldview for medical professions 2019 - Shogar, Ibrahim (2019)
Implications of the Worldview on Thought and Life Implications of the word view on thought (at individual level) It gives meaning and purpose to our life. Provides the systematic answers to the ultimate / cosmic questions; Interprets the being as whole and identifies between means and goals; Gives meaning to human life and establishes ethical commitment; Identify role of human being in relation to other creatures; Establishes the theoretical principles for practical way of life; Implications of the word view on life (at individual & collective levels) Creates the essences of unity and harmony in community; Identifies the different communities and civilizations; Establishes the basic principles of social order and rules for living, with regard to how to satisfy the basic human needs; Protects the community from disintegration